2015
DOI: 10.1371/journal.pone.0126747
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Stage Parasitaemia and Age Determine Plasmodium falciparum and P. vivax Gametocytaemia in Papua New Guinea

Abstract: A better understanding of human-to-mosquito transmission is crucial to control malaria. In order to assess factors associated with gametocyte carriage, 2083 samples were collected in a cross-sectional survey in Papua New Guinea. Plasmodium species were detected by light microscopy and qPCR and gametocytes by detection of pfs25 and pvs25 mRNA transcripts by reverse-transcriptase PCR (qRT-PCR). The parasite prevalence by PCR was 18.5% for Plasmodium falciparum and 13.0% for P. vivax. 52.5% of all infections were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
153
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(180 citation statements)
references
References 44 publications
(68 reference statements)
20
153
3
4
Order By: Relevance
“…dirus . We also found that parasitemia is as good a predictor of infectivity as gametocytemia, consistent with a previous report that for P. vivax parasitemia and gametocytemia are tightly linked (Koepfli et al, 2015). That gametocyte counts did not yield a stronger correlation with mosquito infectivity may also be due to our inability to differentiate fully mature gametocytes from early non-infectious stages of gametocytes.…”
Section: Discussionsupporting
confidence: 92%
“…dirus . We also found that parasitemia is as good a predictor of infectivity as gametocytemia, consistent with a previous report that for P. vivax parasitemia and gametocytemia are tightly linked (Koepfli et al, 2015). That gametocyte counts did not yield a stronger correlation with mosquito infectivity may also be due to our inability to differentiate fully mature gametocytes from early non-infectious stages of gametocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Only four studies, two that used microscopy [18, 26] and two that used molecular methods [21, 27] reported age-distributions similar to what we detected, with higher prevalence of and proportion of infections with gametocytes in school-age children. The present paper is the first report on the epidemiology of gametocyte infections in Malawi.…”
Section: Discussionsupporting
confidence: 75%
“…Molecular gametocyte detection methods have become increasingly common in the past 15 years, though typically they have been used in clinical trials among symptomatic populations and/or exclusively in young children [3340]. Only a few studies have used molecular methods to describe population gametocyte epidemiology [21, 25, 27, 28, 41]. Previous research from southern Malawi found that school-age children have the highest prevalence of infection [42], but their gametocyte carriage and contribution to transmission remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…running DNA corresponding to 4 μL whole blood) a sample would be above the dynamic range of ddPCR if above 0.5% of all red blood cells were infected. This is very rarely the case; based on qPCR in a cross-sectional survey in PNG 12/365 P. falciparum and none out of 270  P. vivax positive samples were above this density7. Samples with parasitemia >0.5% can easily be identified, as all droplets in the ddPCR reaction are positive.…”
Section: Discussionmentioning
confidence: 94%
“…The ability of different diagnostic tools to detect infections34, the severity of clinical symptoms56, and transmission potential78 are all closely related to parasite densities. Parasite densities also show pronounced age patterns, reflecting lifetime exposure and naturally acquired immunity on a population level7. On a programmatic level, malaria control programs require an understanding of parasite densities and their distribution in the general population to estimate the proportion of infections below the limit of detection of field-deployable diagnostic tools such as light microscopy (LM) or rapid diagnostic tests.…”
mentioning
confidence: 99%